KEPENTINGAN AMERIKA SERIKAT MENGHAPUS INDONESIA SEBAGAI NEGARA BERKEMBANG - An Nisa Fitriyah; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The focus of this paper is to explain the interest of the United States in eliminating Indonesia from the category of developing countries. The United States through the USTR considers that several indicators of the regulations they set on trade have shown that Indonesia is not a developing country that deserves to receive subsidized facilities in their trade cooperation. That is why by taking into account the country's per capita income and the joining of Indonesia as a member of the G20 countries, then Indonesia is categorized as a developed country This paper uses the perspective of Neoliberalism which focuses on the theory of the National Interest. By using the theory of national interest, this study aims to reveal the interests of the United States in eliminating Indonesia from the category of developing countries. This study shows that the interests of the United States in eliminating Indonesia from the category of developing countries are in order to maintain Indonesia's important role in the United States, increasing excise tariffs, political interests, opening foreign markets and fighting unfair trade, fair trade, and achieving organizational excellence. Keywords: Interest, USTR, Trade